Digital Transformation of Mosque Finance Through ERP System Implementation - Amalina Nur Arifah; Ana Rimbasari; Nur Irsyad Musthafa (Owner : Riset dan Jurnal Akuntansi, 2026)
As Islamic philanthropic initiatives expand, the digitalization of mosque financial management is becoming increasingly vital for ensuring transparency and accountability in the management of Zakat, Infaq, and Waqf (ZISWAF) funds. This research evaluates how four specific Enterprise Resource Planning (ERP) systems SIPZIS, Ikhlas App, Maslam, and a dedicated web-based platform perform in terms of transparency, efficiency, and user acceptance. We utilized a quantitative cross-sectional approach, gathering data from 40 respondents across four mosques in Indonesia. The sample consisted of 5 administrative staff and 5 congregants from each mosque, though actual distribution per mosque ranged from 9 to 11 respondents due to field conditions. Data were analyzed using one-way ANOVA and multiple regression analysis. The results indicate significant performance variations among the systems regarding transparency (F = 3.120, p = 0.037) and efficiency (F = 2.890, p = 0.049). Furthermore, the regression model (R² = 0.681) suggests that while both factors are important, transparency is the primary driver of user perception (? = 0.450, p = 0.001). These outcomes underscore that for financial technology to be accepted in Islamic institutions, the ability to report transparently is crucial for building trust among the congregation. This study fills a gap in the literature by comparing different ERPs in a faith-based setting and offers actionable insights for developers and mosque administrators aiming to improve digital governance.